Sponge community variation along the Apulian coasts (Otranto Strait) over a pluri-decennial time span. Does water warming drive a sponge diversity increasing in the Mediterranean Sea? - Costa, G.; Bavestrello, G.; Micaroni, V.; Pansini, M.; Strano, F.; Bertolino, M. (Journal of the Marine Biological Association of the United Kingdom, 2019)
Climate change and heavy anthropic pressures are giving rise to important modifications in the rocky benthic communities of the Mediterranean Sea. In particular, sponge assemblages have been deeply affected due to the susceptibility of some species to dramatic phenomena such as mass mortalities or widespread variations in the abundance of other species. For this reason, long-term biodiversity monitoring of the sponge assemblages is important for understanding the direction of changes over time. We studied the sponge fauna living off Tricase Porto (Otranto Strait) and compared its composition with the results of a study conducted in the same area 50 years ago. The comparison indicated that the sponge diversity of this area has strongly increased in the last 50 years and a large number of the sponges recorded in the old survey are still present in the recent community. This evidence matches with other results obtained from different localities of the Mediterranean Sea indicating an increase of sponge diversity, possibly due to the present water warming. The description of two new Demosponge species, Diplastrella boeroi sp. nov. and Spirastrella angulata sp. nov., is also provided.